Automatic generation of OpenDrive roads from road measurements - Shi, Han (My University, 2011)
VTI, Swedish National Road and Transport Research Institute is an independent, research institute in the transport sector. Human Behaviour Analysis in the transport system is VTI's most important responsibility. VTI is developing auto driving system, which needs road information for the simulator. The only data format that the simulator supported is OpenDRIVE data format, unfortunately we do not have an existing data source which is OpenDRIVE data format. Therefore one needs to convert the other kind of GPS data source to OpenDRIVE data format. Then GPS data from OpenStreetMap has been chosen as the source of this project. What the program needs to do is tracing road that described in OpenStreetMap data and converting map information to OpenDRIVE data format. The result is reasonable and good enough so that VTI could use this way and program to generate OpenDRIVE file that they want.
Keywords: Datavetenskap (datalogi); Computer Science